KESADARAN HUKUM SERTIFIKASI HALAL PELAKU USAHA RUMAH MAKAN DI KOTA MALANG - Hassanalwildan Ahmad Zain; Fifik Wiryani; Idaul Hasanah (Indonesia Law Reform Journal, 2021)
This study examines the legal awareness of halal certification of restaurant businesses in Malang. Considering law No. 33 of 2014 on Halal Product Guarantee has been enacted for 5 years, the obligation of halal certification should have been carried out. Moreover, in malang area which is notabene one of the cities with the highest number of universities in East Java. This study has two formulations on how to awareness of halal certification law of restaurant businesses in Malang and how to implement halal certification procedures in LPPOM MUI East Java. The purpose of this study is to measure legal awareness of restaurant businesses in Malang related to halal certification and halal certification management procedures. This research is a sociological juridical research using 2 (two) data collection techniques, namely field research and library research. The theory used is the theory of legal awareness as the basis of analysis in this study. The results of this study are as follows: First, legal awareness of restaurant businesses in Malang related to halal certification has not been maximized because there are indicators and elements that are not fulfilled properly. Second, the process of implementing halal certification from both LPPOM MUI and business actors is in accordance with the provisions that have been given